Diversity and geographical distribution of phytoplasmas infecting China-tree in Argentina - Arneodo, J. D.; Marini, D. C.; Galdeano, E.; Meneguzzi, N.; Bacci, M.; Domecq, C.; Nome, S. F.; Conci, L. R. (Blackwell Publishing, 2007)
Yellows diseases associated with phytoplasmas cause high mortality in China-tree (Melia azedarach) in Argentina, but there has been no previous large-scale survey to determine their diversity and geographical distribution. To assess the presence and identity of phytoplasmas affecting this species throughout the country, 425 samples of symptomatic trees collected at different geographic locations were analysed by a polymerase chain reaction (using universal and group-specific primers) and restriction fragment length polymorphism. Phytoplasmas belonging to 16SrIII-B group were detected at almost every location sampled, whereas 16SrXIII-C group phytoplasmas, reported for the first time in Argentina, were only found in two regions sharing similar agro-ecological characteristics (Northeast provinces and Tucuman). Double infections with 16SrIII-B and 16SrXIII-C group phytoplasmas were also recorded. Nucleotide sequencing of the 16S rDNA of three Argentinian 16SrXIII-C group phytoplasma isolates revealed high identity (99.6-99.3%) with the CbY1 isolate reported from Bolivia.
Keywords: Melia azedarach; phytoplasmas; 16SrIII; 16SrXIII; epidemiology; Argentina